The Influence of Tax Morale and Understanding Tri Nga on Tax Compliance Through Accounting Understanding in Umkm - Alimuddin, Irmawati; Leo, Muarif (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This research aims to provide in-depth insight into the factors that influence the level of tax compliance of MSMEs. The analysis techniques used are descriptive analysis, validity test, reliability test. classical assumption test. Then, regression analysis and Sobel test to test the influence of intervening variables. The results of the research show that Tax Morale has a positive and significant effect on Accounting Understanding, Tri Nga Understanding has a positive and insignificant effect on Accounting Understanding, Tax Morale has a positive and significant effect on Tax Compliance, Tri Nga Understanding Nga has a positive and significant effect on Tax Compliance. Understanding Accounting has a positive and not significant effect on Tax Compliance, Tax Morale has a Positive and not significant effect on Tax Compliance through understanding Accounting, Understanding Tri Nga has a Positive and not significant effect on Tax Compliance through understanding Accounting